Contentious framings: Swedish civil society actors’ experience of hate speech, threats, and harassment from multiple perpetrators - Scaramuzzino, Gabriella; Scaramuzzino, Roberto (Journal of Political Sociology, 2025)
This article explores civil society actors’ experiences of hate speech, threats, and harassment; specifically those of the harassers or perpetrators. The article draws on a qualitative study with elected representatives, paid employees, and volunteers in different Swedish Civil Society Organisations and social movements. The phenomena are analysed from a relational perspective and theories that frame civil society as a contentious civil sphere. The article offers a complex picture of multiple perpetrators; from anonymous senders and organised crime members to counter movements. The findings show the sectoral, legal, and moral boundaries that are drawn between victims and perpetrators.